The production of antibody by invading B cells is required for the clearance of rabies virus from the central nervous system. - D Craig Hooper; Timothy W Phares; Marzena J Fabis; Anirban Roy (Public Library of Science (PLoS), 2009)
The pathogenesis of rabies is associated with the inability to deliver immune effectors across the blood-brain barrier and to clear virulent rabies virus from CNS tissues. However, the mechanisms that facilitate immune effector entry into CNS tissues are induced by infection with attenuated rabies virus.Infection of normal mice with attenuated rabies virus but not immunization with killed virus can promote the clearance of pathogenic rabies virus from the CNS. T cell activity in B cell-deficient mice can control the replication of attenuated virus in the CNS, but viral mRNA persists. Low levels of passively administered rabies virus-neutralizing antibody reach infected cells in the cerebellum of B cell-deficient mice but are not sufficient to mediate virus clearance. Production of rabies virus-specific antibody by B cells invading CNS tissues is required for this process, and a substantial proportion of the B cells that accumulate in the CNS of mice infected with attenuated rabies virus produce virus-specific antibodies.The mechanisms required for immune effectors to enter rabies virus-infected tissues are induced by infection with attenuated rabies virus but not by infection with pathogenic rabies viruses or immunization with killed virus. T cell activities can inhibit rabies virus replication, but the production of rabies virus-specific antibodies by infiltrating B cells, as opposed to the leakage of circulating antibody across the BBB, is critical to elimination of the virus. These findings suggest that a pathogenic rabies virus infection may be treatable after the virus has reached the CNS tissues, providing that the appropriate immune effectors can be targeted to the infected tissues.